2009
DOI: 10.1111/j.1741-1130.2009.00222.x
|View full text |Cite
|
Sign up to set email alerts
|

Current and Future Concerns of Older Parents of Sons and Daughters With Intellectual Disabilities

Abstract: Increasingly greater numbers of older parents are providing care at home for their sons and daughters with intellectual disabilities. As attention needs to be paid to the supports needed by such families to assist them with their caregiving activities, it is prudent to identify the types of supports that will be needed when the parents are no longer able to provide care. Working with a cohort of older parent carers in Prince Edward Island, Canada, the authors undertook to examine older carer concerns and plann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 38 publications
1
34
0
2
Order By: Relevance
“…In a Canadian study, Weeks et al . () used interviews ( n = 43) to examine current and future concerns of ageing family carers of older people with ID. The authors found that the main concern expressed by participants was worry about the future followed by financial concerns, appropriate housing and care options.…”
Section: Resultsmentioning
confidence: 99%
“…In a Canadian study, Weeks et al . () used interviews ( n = 43) to examine current and future concerns of ageing family carers of older people with ID. The authors found that the main concern expressed by participants was worry about the future followed by financial concerns, appropriate housing and care options.…”
Section: Resultsmentioning
confidence: 99%
“…In some cases, that parenting role can span up to seven decades (Ryan, Taggart, Truesdale‐Kennedy, & Slevin, ). Research has shown that many parents and siblings feel anxiety about the long‐term care plans for their adult relative with IDD (Davys & Haigh, ; Davys, Mitchell, & Haigh, ; Freedman, Krauss, & Seltzer, ; Weeks, Nilsson, Bryanton, & Kozma, ). Previous research has found that caregivers in this group are likely to be socially and economically disadvantaged and at greater risk than most to develop serious health issues (Black & McKendrick, ; McConkey, ; Ryan et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Not surprisingly, parents of adults with IDD report behavior problems as a consistent predictor of poor adjustment and cite major concerns regarding long-term planning for accommodation, future support, guardianship, and the need for more formal supports in the community (Minnes & Woodford, 2004;Minnes, Woodford, & Passey, 2007;Weeks, Nilson, Bryanton, & Kozma, 2009). Parents of adults with IDD may differ from parents of youth with IDD in terms of the types of services they need and receive and the barriers to such service use .…”
Section: Research On Caregiversmentioning
confidence: 95%